The Mediating Role of Compensation to the Effect of Work Competency and Workload on Organizational Commitments’ Civil Servant: The Study of Regional Civil Service Agency in East Java Province - Rajma Tri Handoko* (Universitas Airlangga, 2019)
One important aspect of the organization was maintaining employee presence and reviewing the organizational commitments held by each individual. High commitment made individuals concerned with the future of the organization and tried to make the organization a better direction, on the contrary, individuals with low commitment would prioritize themselves or their groups and did not have the desire to make the organization towards a better direction. High work competency, an employee would be able to do much for the organization, conversely with low competency an employee would not be able to complete his duties as well as possible, which ultimately hamper the achievement of organizational goals. The distribution of employee workload that had not appropriate can make employees not have less than optimal performance. Compensation could be an incentive for someone to do an activity to get the best results, compensation needed to be raised so that employees could carry out maximum performance. The purpose of this study was to analyzing and testing the effect of work competence and workload on organizational commitment through compensation to Civil Servants in the Regional Civil Service Agency of East Java Province. This research used a quantitative approach with an explanative design. The results of this study provided several conclusions, including: 1.) Work competence had a significant positive effect on compensation; 2.) Workload had a significant effect on compensation; 3.) Work competence had a significant positive effect on organizational commitment; 4.) Workload had a significant positive effect on organizational commitment; 5.) Compensation had a significant positive effect on organizational commitment; 6.) Compensation became an intervening variable on the effect of work competence and workload on organizational commitment.